Evaluating the Performances of Digital Data Transmission Links on a Client-Server Network Model - Akintola, Grace Bunmi; Falade, Polra Victor (International Journal of Scientific Research in Computer Science and Engineering, 2024)
Having smooth communication and high-quality performance over IP networks in the real world has been the goal of all businesses and organizations to enhance their daily business operations through having easy access to resources and data over the network without any obstructions. Therefore, Riverbed modeler software, also known as OPNET, was used in this paper to simulate a client-server model communication over an IP network as well as evaluate the performances of the three digital data transmission links (also known as data rate links) in three provided scenarios using some selected statistics which were used for the analysis of the obtained results across all the Scenarios. T1 link was used for the first scenario in communicating among all the offices (Manchester, Sydney, Chicago, and the Call Center (Nigeria)) and shows a non-optimized network performance as there is the presence of clogs (delay) in the network. The T1 link was replaced with T3 links, giving better network performance as it could transmit packets. Although network delay and packet delivery to the assigned destination were reduced, the T3 link was replaced with the OCI link to obtain better results in transmitting network packets.